"A human being like other victims": the media framing of trans homicide in the United States - DeJong, Christina (Critical criminology, 2021)
A growing awareness of violence against LGBTQ + individuals has led to an increase in media coverage of the homicides of trans people in the United States. Media accounts involve powerful narratives which are subjective, biased, and imbued with meaning. These narratives employ "frames" that impact public perception of populations. Studies have demonstrated differences in the ways that trans victims of homicide are framed compared to cis victims, specifically regarding responsibility for the violence inflicted upon them. Trans victims are more likely to be constructed as "deviants" or criminals who are deserving of or responsible for their own homicides. In addition, these victims are framed as deceivers who deliberately obscure their gender modality from offenders, thus facilitating violent retaliation. The present study employs a mixed methods approach to analyze articles published in news media outlets about the twenty-six trans people killed in 2018. Our analysis identified more positive frames than negative frames employed by agents of social control, such as media and law enforcement, that inform narratives surrounding this unique form of violence. Yet, efforts still need to be undertaken to involve trans voices, to humanize those who have lost their lives, and most importantly, to prevent this violence. This article discusses implications for how these organizations can begin to transform these narratives to describe accurately trans victims of homicide.